Effect of Blumea balsamifera extract on the phase and morphology of calcium oxalate crystals - Charlimagne M. Montealegre; Rizalinda L. De Leon (Asian Journal of Urology)
Objective: Calcium oxalate crystals are found in majority of kidney stones with calcium oxalate monohydrate (COM) as one of the primary types of kidney stones. Various methods of treatment exist, including herbal treatment in the Philippines that uses the medicinal herb Blumea balsamifera (B. balsamifera). Methods: The effect of B. balsamifera extract on the morphology of calcium oxalate crystals was studied by light microscopy, image analysis, powder X-ray diffraction and scanning electron microscopy. Results: The extract decreased the crystal size by 5.22%–82.62% depending on the degree of supersaturation. Through analysis of the projected area of the crystals, the extract was found to shift the phase of the crystals from COM to calcium oxalate dihydrate (COD). This shift in phase is significant with a COM to COD shift of 88.26% at 0.5 mg/mL of extract and 91.53% at 1.0 mg/mL of extract. Scanning election microscopic (SEM) images revealed aggregation of crystals at 0 mg/mL of extract. At 1.0 mg/mL of extract, the scanning electron micrographs showed discernible crystal unit boundaries. Conclusion: B. balsamifera extract was observed to have decreased crystal size, shifted crystal phase from COM to COD and prevented the aggregation of calcium oxalate crystals.